Automation of Bricket Charcoal Press Machine to Increase Production Capacity in Kampoeng Oase Ondomohen Surabaya - Aulia Annisa; Khodijah Amiroh; Rizqa Amelia Zunaidi; Annisa Rizkyta Nabilah Junaidi; Muhammad Ardiansyah Al Faiz (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2023)
Kampoeng Oase, is one of the educational village tourist destinations located on Jalan Ondomohen Magersari V, Ketabang Village, Genteng District, Surabaya City. It is named the educational village because this village has succeeded in processing waste into something that has a high selling value. But behind the success in processing the waste, there are some problems in Kampoeng Oase, especially in producing charcoal briquettes. Problems related to the aspect of increasing production capacity have been carried out by automated tools for making charcoal briquettes using the latest technology. By using an automatic press machine, Kampoeng Oase can now produce charcoal briquettes with a minimal amount of labor and a shorter processing time compared to the manual production process. By utilizing waste in charcoal briquettes, it can solve problems related to waste management and protect the environment and help encourage a circular economy to improve welfare, especially for the people of Kampoeng Oase Ondomohen Surabaya.